A fluorinated silicon carbide composite material and preparation method thereof
By filling the porous hard carbon with fluorinated silicon carbide and combining the support and conduction of carbon nanotubes, the problem of volume expansion and new interface reaction of the negative electrode material of the lithium-ion battery is solved during the charging and discharge process, and the first Coulomb efficiency and cycling performance of the battery are improved.
Patent Information
- Application Number
- CN202411756070.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The existing lithium-ion battery negative electrode material, silicon-carbon composite, has volume expansion and new interface reactions during charging and discharging, resulting in a decline in battery performance and poor Coulomb efficiency and circulation performance for the first time.
By preparing porous hard carbon as a hard carbon precursor and filling its pores with fluorinated silicon carbide, it directly fluorinated silicon carbide to modify the silicon material, combining the support and conduction of carbon nanotubes to form a fluorinated silicon carbide composite material.
The expansion of the silicon carbide negative electrode material during charging is improved, the first Coulomb efficiency and cycling performance is improved, and the stability and efficiency of the battery are ensured.
Smart Images

Figure CN119230805B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a fluorinated silicon carbide composite material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used in new energy vehicles and energy storage. Silicon is considered to be the most promising negative electrode material for lithium-ion batteries due to its high theoretical capacity. However, the silicon negative electrode has a huge volume expansion during the charging and discharging process, and silicon particles are prone to pulverization. In addition, the new interface caused by the continuous pulverization of silicon particles constantly reacts with the electrolyte, and the solid electrolyte membrane (SEI) on the surface is constantly destroyed and reformed, rapidly consuming electrolytes and lithium ions, causing the battery performance to continue to decline. The unstable SEI membrane reduces the capacity of silicon particles and also reduces the coulombic efficiency.
[0003] With the gradual industrialization of silicon materials, silicon-carbon materials with better electrochemical properties have become a key research and development direction. In traditional technologies, graphite and silicon particles are usually composited to improve energy density and fast charging performance, but the expansion rates of silicon particles and graphite materials are relatively large, resulting in unstable structure and poor cycle performance of the battery cell during cyclic charging and discharging, as well as low first coulomb efficiency. In the prior art, the first coulomb efficiency is improved by designing a multi-level core-shell structured nano-silicon-carbon composite material and modifying it with fluoride. For example, Chinese patent application CN109286014A discloses a surface-modified silicon-carbon composite material and its preparation method and application, first preparing nano-silicon for carbon coating to obtain a silicon-carbon composite material, and then compounding the nano-silicon-carbon composite material and fluoride by ball milling to obtain a surface-modified silicon-carbon composite material. Chinese patent application CN115799474 A discloses a preparation method and application of a fluorinated silicon-carbon negative electrode material, by co-heat-treating an amorphous carbon-coated silicon negative electrode material with polyvinylidene fluoride powder to obtain a fluorinated silicon-carbon negative electrode material. Both of the above methods react through contact between solids, and the contact reaction between fluoride and silicon-carbon material is limited, the fluorination surface is small, and the fluorination effect is not good. In addition, these silicon materials are completely coated with fluoride layers, so that lithium can only migrate through solid phase diffusion, resulting in a low migration rate. Chinese patent application CN115939342A discloses a nano-silicon-carbon composite material, first preparing porous hard carbon, then the porous hard carbon and a fluorine source are subjected to vapor deposition fluorination reaction to obtain fluorinated porous hard carbon, and then the fluorinated porous hard carbon is mixed with nano-silicon particles and ball-milled and calcined to obtain a nano-silicon-carbon composite material. Although this method fluorinates the surface and internal surface of porous hard carbon, when the fluorine source is vapor-deposited into the pores of porous hard carbon, the fluoride that is preferentially deposited on the surface and entrance of the pores is very easy to block the pores, so that the depth and amount of fluorine entering the curved pores of porous hard carbon are very limited, the fluorination effect is limited, and what is fluorinated is porous hard carbon, and it does not actually work directly on the surface of the silicon material. Summary of the invention
[0004] The purpose of the present invention is to provide a fluorinated silicon carbide composite material, which can better fluorinate and modify the silicon carbide negative electrode material, improve the expansion of the material during charging, and improve its first coulombic efficiency and cycle performance.
[0005] The technical solution of the present invention is:
[0006] A fluorinated silicon carbide composite material comprises porous hard carbon and fluorinated silicon carbide, wherein the porous hard carbon supports carbon nanotubes, and the pores of the porous hard carbon are filled with the fluorinated silicon carbide.
[0007] In the fluorinated silicon carbide composite material of the present invention, silicon carbide is directly fluorinated first and then filled in the pores of porous hard carbon. The direct fluorination modification of silicon carbide allows the fluoride to directly modify the silicon material, stabilize the structure of the silicon material, improve the volume expansion of the silicon material, and achieve a good fluorination effect. In addition, the fluorinated silicon carbide is filled in the pores of the porous hard carbon, and the porous hard carbon limits the expansion and contraction deformation of the fluorinated silicon carbide in the form of a porous shell, while also providing good electrical conductivity; the carbon nanotubes supported in the porous hard carbon structure, on the one hand, play a role in connecting and conducting current, and on the other hand, serve as a support for the porous hard carbon pore structure, preventing its structural collapse during the repeated expansion and contraction deformation of silicon carbide.
[0008] Preferably, the carbon nanotubes are single-walled carbon nanotubes. Compared with multi-walled carbon nanotubes, single-walled carbon nanotubes have a larger number of the same mass and can be more widely distributed in hard carbon to form a three-dimensional network. In addition, single-walled carbon nanotubes have higher strength and toughness, and the network formed has better support and anti-cracking effects.
[0009] Preferably, the single-walled carbon nanotube has a diameter of 1 to 3 nm, a length of 2 to 5 μm, and an aspect ratio of 1000 to 5000. The single-walled carbon nanotube selected according to this requirement does not affect the filling of fluorinated silicon carbide in the pores.
[0010] Preferably, the porous hard carbon is isotactic polypropylene cracked carbon. Isotactic polypropylene tends to become granular during crystallization, and the particle size can be controlled by controlling the crystallization conditions, thereby controlling the microstructure of the prepared fluorinated silicon carbide composite material to achieve the desired performance.
[0011] The present invention also provides a method for preparing the fluorinated silicon carbide composite material, comprising the following steps:
[0012] Step 1, preparing a porous polymer matrix;
[0013] Add a mixture of a polymer, a good solvent for the polymer and a poor solvent in a volume ratio of 10:1-5 into a container and stir until a homogeneous solution is formed, add the carbon nanotube slurry and mix evenly; pour into a mold, place in a vacuum oven at 10-40°C and stand for 3-12 hours, wherein the vacuum degree of the vacuum oven is ≤-90kPa; naturally volatilize the solvent at 20-25°C to obtain a porous polymer matrix;
[0014] Step 2, polydimethylsiloxane and perfluoropolyether oil are mixed evenly at a mass ratio of 10:0.1-0.5 to obtain a mixed impregnation liquid, and then poured into the obtained porous polymer matrix to obtain a casting body;
[0015] Step 3, the obtained casting body is subjected to the following reactions in sequence to obtain a fluorinated silicon carbide composite material:
[0016] A. Under vacuum degree ≤ -90kPa, react at 450-600℃ for 6-10h;
[0017] B. Under the protection of inert gas, react at 1000-1500℃ for 6-10h. The inert gas here refers to nitrogen, argon, etc.
[0018] The preparation method of the fluorinated silicon carbide composite material of the present invention comprises the following steps: in step 1, after the polymer forms a homogeneous solution in its good solvent and poor solvent, a carbon nanotube slurry is added, and the carbon nanotubes are evenly dispersed between the molecules of the polymer. When standing in a vacuum oven, the polymer is phase-separated and enriched between its good solvent and poor solvent. After 10 to 40° C. and 3 to 12 hours, the good solvent and the poor solvent evaporate rapidly, causing the polymer to crystallize and precipitate. Under the action of the good solvent and the poor solvent evaporating rapidly together, the crystal grains form a polymer porous structure. After the solvent is naturally evaporated at 20 to 25° C., the porous structure matures and sets. In step 2, a casting body is obtained by pouring a mixed impregnation liquid containing polydimethylsiloxane and perfluoropolyether oil, and the pores of the obtained polymer porous structure are filled with the mixed liquid of polydimethylsiloxane and perfluoropolyether oil. In step A of step three, the Si-Si bonds in polydimethylsiloxane are broken and rearranged at 450-600°C, converted into Si-C bonds, and low-molecular carbosilane is generated; as the temperature continues to rise, dehydrogenation and demethanization condensation reactions occur between carbosilane molecules to gradually increase the molecular weight to generate polycarbosilane; the fluorine element in the perfluoropolyether oil mixed in the polydimethylsiloxane is compounded into the finished polycarbosilane during the breaking and rearrangement of the Si-Si bonds of the polydimethylsiloxane; after sintering at 1000-1500°C in step B, the porous structure of the polymer is carbonized and cracked, and the polycarbosilane is inorganicized into silicon carbide and fluorinated; thereby, a composite structure in which the pores of the porous hard carbon are filled with fluorinated silicon carbide, and carbon nanotubes are supported in the porous hard carbon, which is now a fluorinated silicon carbide composite material.
[0019] Since perfluoropolyether oil has a wide operating temperature range, high stability and oxidation resistance, little change in viscosity with temperature, and extremely low volatility, it is very suitable for pouring into porous polymer matrices during fluorination.
[0020] The inventive concept of the present invention is: one of the reasons why the prior art has a poor effect on improving the expansion and coulomb efficiency of silicon-based materials is the incomplete fluorination of silicon-based materials; and there are two reasons for the incomplete fluorination of silicon-based materials. One is that the silicon material is not directly fluorinated, but other materials are fluorinated around the silicon material; the other is that the fluorination is uneven and the distribution of silicon in the material is uneven. In order to solve these problems, the method adopted by the present invention is first to directly fluorinate the silicon material to make fluorinated silicon carbide; the second is to construct a structure that can make the silicon material evenly distributed, and guide the silicon material to be evenly distributed therein. Based on the above concept, the present invention first prepares a porous polymer matrix as a precursor of hard carbon, and then adsorbs polydimethylsiloxane and perfluoropolyether oil through capillary action to diffuse in the pores to achieve uniform distribution, and then carbonizes, thereby achieving direct, uniform, comprehensive fluorination and uniform distribution of silicon materials.
[0021] Preferably, the polymer is isotactic polypropylene; the good solvent is at least one of xylene, toluene, benzene and decalin; and the poor solvent is at least one of butanone, ethanol, methanol, n-butanol and n-propanol.
[0022] When isotactic polypropylene is used to prepare a porous polymer matrix, the porous polymer matrix formed is easy to form particles. By controlling different concentrations during the preparation, particles with different particle size distributions can be obtained. Such particles are particularly suitable for making battery negative electrode materials after carbonization.
[0023] More preferably, the mass ratio of the isotactic polypropylene to the carbon nanotubes is 100:1-5, the concentration of the isotactic polypropylene in the mixed solution is 1-50 mg / mL, and the dissolution temperature is 120-140°C. It is relatively easy to obtain a homogeneous solution of isotactic polypropylene at 1-50 mg / mL and 120-140°C, so that the carbon nanotube slurry can be evenly dispersed therein. The isotactic polypropylene of such a concentration is dispersed in a mixed solution of the above-mentioned good solvent and the poor solvent in a volume ratio of 10:1-5, and the pore size obtained in the polymer matrix formed later is very suitable for the mixed impregnation solution formed by mixing polydimethylsiloxane and perfluoropolyether oil in a mass ratio of 10:0.1-0.5 to penetrate by capillary action, and the penetration speed is fast.
[0024] Preferably, the perfluoropolyether oil is CF3CF2CF2O(CF(CF3)CF2O)mCF2CF3, and the number average molecular weight is 2000 to 4500. In this way, the perfluoropolyether oil has good fluidity and wettability, and can easily enter the pores of the porous polymer matrix.
[0025] Preferably, the pouring method in step 2 is:
[0026] A. completely immersing the porous polymer matrix in the mixed impregnation liquid, and then placing it in a vacuum infiltration device;
[0027] B. Evacuate the mixture, maintain the vacuum degree at -50 to -70 kPa for 30 to 60 seconds, and release the pressure to allow the mixed impregnation liquid to penetrate into the porous polymer matrix; repeat 2 to 3 times.
[0028] By adopting the above-mentioned pouring method, the gas in the pores of the porous polymer matrix can be quickly exhausted, so that the mixed permeable liquid containing polydimethylsiloxane and perfluoropolyether oil can be filled more quickly and completely, thereby avoiding the occurrence of voids.
[0029] The beneficial effects of the present invention are:
[0030] The method of the present invention prepares a porous polymer matrix as a porous hard carbon precursor, and evenly disperses carbon nanotubes therein, and then casts the porous polymer matrix with a mixed solution of polydimethylsiloxane and perfluoropolyether oil. In the subsequent heating and sintering process, the porous hard carbon precursor is carbonized and fluorinated silicon carbide is generated in the pores, thereby achieving uniform fluorination modification of the silicon carbide itself, thereby better improving its expansion when used as a battery material and improving its cycle performance; the hard carbon of the fluorinated silicon carbide is wrapped in the form of a pore shell to limit the deformation of the silicon fluoride and provide electronic conductivity; the carbon nanotubes penetrate the hard carbon to form a fast channel for electron transmission, further improving the conductivity of the material and giving it a good first coulomb efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image of the porous polypropylene matrix prepared in Example 1. DETAILED DESCRIPTION
[0032] The present invention is described in detail below with reference to the examples. The polydimethylsiloxane used in the following examples is a commercial product, for example, it can be obtained by polymerizing a prepolymer of model SYLGARD 184 produced by Dow Corning Company of the United States.
[0033] Example 1
[0034] A fluorinated silicon carbide composite material is prepared as follows:
[0035] Step 1: Preparation of porous polypropylene matrix
[0036] Isotactic polypropylene is added to a container, and then a mixed solution of xylene and butanone in a volume ratio of 9:1 is added, and the mixture is stirred at 130°C until a homogeneous solution is formed, and a single-walled carbon nanotube slurry is added and mixed evenly, wherein: the mass ratio of isotactic polypropylene to single-walled carbon nanotubes is 100:3, and the concentration of isotactic polypropylene in the mixed solution is 20 mg / mL; the single-walled carbon nanotubes have a diameter of 1 nm to 3 nm, a length of 2 μm to 5 μm, and an aspect ratio of 1000 to 5000.
[0037] Pour the mixture into a mold, place it in a vacuum oven at 30° C. and let it stand for 6 hours, wherein the vacuum degree of the vacuum oven is -95 kPa; the solvent is naturally evaporated at 20-25° C. to obtain a porous polypropylene matrix. Figure 1 This is a scanning electron microscope image of the porous polypropylene matrix prepared in this example. It can be seen from the image that it has a structure of many intersecting holes.
[0038] Step 2: Evenly mix polydimethylsiloxane and perfluoropolyether oil in a mass ratio of 10:0.3 to obtain a mixed impregnation liquid, wherein: polydimethylsiloxane is obtained by polymerization of a prepolymer model SYLGARD 184 produced by Dow Corning Corporation of the United States; and the perfluoropolyether oil is CF3CF2CF2O(CF(CF3)CF2O)mCF2CF3, with a number average molecular weight of 3000.
[0039] The porous polypropylene matrix is completely immersed in the mixed impregnation liquid, and then placed in a vacuum infiltration device; vacuum is drawn, and the vacuum degree and pressure are maintained at -50 kPa for 40 seconds, and the pressure is released to allow the mixed impregnation liquid to penetrate into the porous polypropylene matrix; this is repeated twice to obtain a cast body.
[0040] Step 3, the obtained casting body is subjected to the following reactions in sequence:
[0041] A. Under vacuum degree -95kPa, keep the temperature at 450-500℃ for 8h; B. Under nitrogen protection, keep the temperature at 1000-1050℃ for 8h to obtain fluorinated silicon carbide composite material.
[0042] Example 2
[0043] A fluorinated silicon carbide composite material is prepared as follows:
[0044] Step 1: Preparation of porous polypropylene matrix
[0045] Isotactic polypropylene is added to a container, and then a mixed solution of toluene and ethanol in a volume ratio of 2:1 is added, and the mixture is stirred at 120°C until a homogeneous solution is formed, and a single-walled carbon nanotube slurry is added and mixed evenly, wherein: the mass ratio of isotactic polypropylene to single-walled carbon nanotubes is 100:1, and the concentration of isotactic polypropylene in the mixed solution is 50 mg / mL; the single-walled carbon nanotubes have a diameter of 1 nm to 3 nm, a length of 2 μm to 5 μm, and an aspect ratio of 1000 to 5000.
[0046] Pour into a mold, place in a vacuum oven at 10°C for 3 hours, where the vacuum degree of the vacuum oven is -95 kPa; the solvent evaporates naturally at 20-25°C to obtain a porous polypropylene matrix. The scanning electron microscope image of the porous polypropylene matrix prepared in this embodiment also shows that it has many intersecting pore structures.
[0047] Step 2: Evenly mix polydimethylsiloxane and perfluoropolyether oil in a mass ratio of 10:0.1 to obtain a mixed impregnation liquid, wherein the polydimethylsiloxane is obtained by polymerization of a prepolymer model SYLGARD 184 produced by Dow Corning Corporation of the United States; the perfluoropolyether oil is CF3CF2CF2O(CF(CF3)CF2O)mCF2CF3, and the number average molecular weight is 2000.
[0048] The porous polypropylene matrix is completely immersed in the mixed impregnation liquid, and then placed in a vacuum infiltration device; vacuum is drawn, and the vacuum degree and pressure are maintained at -70 kPa for 60 seconds, and the pressure is released to allow the mixed impregnation liquid to penetrate into the porous polypropylene matrix; this is repeated 3 times to obtain a cast body.
[0049] Step 3, the obtained casting body is subjected to the following reactions in sequence:
[0050] A. Under vacuum degree -95kPa, keep the temperature at 500℃~550℃ for 10h; B. Under nitrogen protection, keep the temperature at 1450℃~1500℃ for 10h to obtain fluorinated silicon carbide composite material.
[0051] Example 3
[0052] A fluorinated silicon carbide composite material is prepared as follows:
[0053] Step 1: Preparation of porous polypropylene matrix
[0054] Isotactic polypropylene is added to a container, and then a mixture of benzene and methanol in a volume ratio of 10:1 is added, and the mixture is stirred at 140°C until a homogeneous solution is formed, and single-walled carbon nanotube slurry is added and mixed evenly, wherein: the mass ratio of isotactic polypropylene to single-walled carbon nanotube is 100:5, and the concentration of isotactic polypropylene in the mixture is 1 mg / mL; the diameter of the single-walled carbon nanotube is 1nm~3nm, the length is 2μm~5μm, and the aspect ratio is 1000~5000.
[0055] Pour into a mold, place in a vacuum oven at 40°C for 12 hours, wherein the vacuum degree of the vacuum oven is -95 kPa; the solvent evaporates naturally at 20-25°C to obtain a porous polypropylene matrix. The scanning electron microscope image of the porous polypropylene matrix prepared in this embodiment shows that it has a mutually interlaced pore structure.
[0056] Step 2: Evenly mix polydimethylsiloxane and perfluoropolyether oil in a mass ratio of 10:0.5 to obtain a mixed impregnation liquid, wherein the polydimethylsiloxane is obtained by polymerization of a prepolymer model SYLGARD 184 produced by Dow Corning Corporation of the United States; the perfluoropolyether oil is CF3CF2CF2O(CF(CF3)CF2O)mCF2CF3, and the number average molecular weight is 4500.
[0057] The porous polypropylene matrix is completely immersed in the mixed impregnation liquid, and then placed in a vacuum infiltration device; vacuum is drawn, and the vacuum degree and pressure are maintained at -60 kPa for 30 seconds, and the pressure is released to allow the mixed impregnation liquid to penetrate into the porous polypropylene matrix; this is repeated 3 times to obtain a cast body.
[0058] Step 3, the obtained casting body is subjected to the following reactions in sequence:
[0059] A. Under vacuum degree -95kPa, keep the temperature at 550-600℃ for 6 hours; B. Under nitrogen protection, keep the temperature at 1300-1350℃ for 6 hours to obtain fluorinated silicon carbide composite material.
[0060] Example 4
[0061] A fluorinated silicon carbide composite material is prepared as follows:
[0062] Step 1: Preparation of porous polypropylene matrix
[0063] Isotactic polypropylene is added to a container, and then a mixture of decalin and n-butanol in a volume ratio of 7:1 is added, and the mixture is stirred at 130° C. until a homogeneous solution is formed, and a single-walled carbon nanotube slurry is added and mixed evenly, wherein: the mass ratio of isotactic polypropylene to single-walled carbon nanotube is 100:2, and the concentration of isotactic polypropylene in the mixture is 30 mg / mL; the single-walled carbon nanotube has a diameter of 1 nm to 3 nm, a length of 2 μm to 5 μm, and an aspect ratio of 1000 to 5000.
[0064] Pour into a mold, place in a vacuum oven at 30°C for 8 hours, wherein the vacuum degree of the vacuum oven is -95 kPa; the solvent evaporates naturally at 20-25°C to obtain a porous polypropylene matrix. The scanning electron microscope image of the porous polypropylene matrix prepared in this embodiment shows that it has a mutually interlaced pore structure.
[0065] Step 2: Evenly mix polydimethylsiloxane and perfluoropolyether oil in a mass ratio of 10:0.2 to obtain a mixed impregnation liquid, wherein the polydimethylsiloxane is obtained by polymerization of a prepolymer model SYLGARD 184 produced by Dow Corning Corporation of the United States; the perfluoropolyether oil is CF3CF2CF2O(CF(CF3)CF2O)mCF2CF3, and the number average molecular weight is 4000.
[0066] The porous polypropylene matrix is completely immersed in the mixed impregnation liquid, and then placed in a vacuum infiltration device; vacuum is drawn, and the vacuum degree and pressure are maintained at -50 kPa for 40 seconds, and the pressure is released to allow the mixed impregnation liquid to penetrate into the porous polypropylene matrix; this is repeated twice to obtain a cast body.
[0067] Step 3, the obtained casting body is subjected to the following reactions in sequence:
[0068] A. Under vacuum degree -95kPa, keep the temperature at 450-500℃ for 8h; B. Under nitrogen protection, keep the temperature at 1000-1050℃ for 8h to obtain fluorinated silicon carbide composite material.
[0069] Example 5
[0070] A fluorinated silicon carbide composite material is prepared as follows:
[0071] Step 1: Preparation of porous polypropylene matrix
[0072] Add isotactic polypropylene to the container, then add a mixture of xylene and n-propanol in a volume ratio of 8:1, stir at 130°C until a homogeneous solution is formed, add multi-walled carbon nanotube slurry and mix evenly, wherein: the mass ratio of isotactic polypropylene to multi-walled carbon nanotubes is 100:4, and the concentration of isotactic polypropylene in the mixture is 5 mg / mL. The solid content of the multi-walled carbon nanotube slurry is 12.5%, the diameter of the multi-walled carbon nanotube is 20~50nm, and the length is 2~5μm.
[0073] Pour into a mold, place in a vacuum oven at 30°C for 10 hours, wherein the vacuum degree of the vacuum oven is -95 kPa; the solvent is naturally evaporated at 20-25°C to obtain a porous polypropylene matrix. The scanning electron microscope image of the porous polypropylene matrix prepared in this embodiment shows that it has a mutually interlaced pore structure.
[0074] Step 2: Evenly mix polydimethylsiloxane and perfluoropolyether oil in a mass ratio of 10:0.4 to obtain a mixed impregnation liquid, wherein the polydimethylsiloxane is obtained by polymerization of a prepolymer model SYLGARD 184 produced by Dow Corning Corporation of the United States; the perfluoropolyether oil is CF3CF2CF2O(CF(CF3)CF2O)mCF2CF3, and the number average molecular weight is 3000.
[0075] The porous polypropylene matrix is completely immersed in the mixed impregnation liquid, and then placed in a vacuum infiltration device; vacuum is drawn, and the vacuum degree and pressure are maintained at -50 kPa for 40 seconds, and the pressure is released to allow the mixed impregnation liquid to penetrate into the porous polypropylene matrix; this is repeated twice to obtain a cast body.
[0076] Step 3, the obtained casting body is subjected to the following reactions in sequence:
[0077] A. Under vacuum degree -95kPa, keep the temperature at 450-500℃ for 8h; B. Under nitrogen protection, keep the temperature at 1000-1050℃ for 8h to obtain fluorinated silicon carbide composite material.
[0078] Comparative Example 1
[0079] A fluorinated silicon carbide composite material was prepared. The only difference between the preparation method and Example 1 was that in step 1, no single-walled carbon nanotube slurry was added in step 1 of this comparative example. The rest was exactly the same as in Example 1.
[0080] Comparative Example 2
[0081] A fluorinated silicon carbide composite material is prepared.
[0082] This comparative example is used for comparison with Example 1. The models and amounts of isotactic polypropylene, xylene, butanone, single-walled carbon nanotube slurry, polydimethylsiloxane and perfluoropolyether oil used in this comparative example are exactly the same, except that: 1. In step one, no single-walled carbon nanotube slurry is added, but the same mass of single-walled carbon nanotubes are compounded in step four; 2. In step two, no casting body of polydimethylsiloxane and perfluoropolyether oil is prepared, but only perfluoropolyether oil is impregnated into porous polypropylene for carbonization to prepare fluorinated carbon material; and in step three, polydimethylsiloxane is made into silicon carbide alone; 3. Fluorinated carbon material, silicon carbide and single-walled carbon nanotubes are compounded in step four. The specific method is as follows:
[0083] Step 1: Preparation of porous polypropylene matrix
[0084] Add isotactic polypropylene to the container, then add a mixture of xylene and butanone in a volume ratio of 9:1, stir at 130°C until a homogeneous solution is formed, and the concentration of isotactic polypropylene in the mixture is 20 mg / mL. Pour into the mold, place in a vacuum oven at 30°C for 6 hours, where the vacuum degree of the vacuum oven is -95 kPa; the solvent is naturally evaporated at 20-25°C to obtain a porous polypropylene matrix.
[0085] Step 2: Preparation of fluorinated carbon material
[0086] The porous polypropylene matrix prepared in step 1 is completely immersed in the perfluoropolyether oil CF3CF2CF2O (CF(CF3)CF2O)mCF2CF3 with a number average molecular weight of 3000, and then placed in a vacuum infiltration device; vacuum is drawn, and the vacuum degree and pressure are maintained at -50kPa for 40s, and the pressure is released to allow the mixed infiltration liquid to penetrate into the porous polypropylene matrix; this is repeated twice to obtain a casting body. The obtained casting body is reacted at 1000-1050°C for 8h under a vacuum degree of -95kPa and nitrogen protection. A fluorinated carbon material is obtained.
[0087] Step 3: Preparation of silicon carbide
[0088] Polydimethylsiloxane (polydimethylsiloxane is obtained by polymerization of a prepolymer model SYLGARD184 produced by Dow Corning Corporation of the United States) is sequentially subjected to the following reactions:
[0089] A. Under vacuum degree -95kPa, keep the temperature at 450-500℃ for 8h; B. Under nitrogen protection, keep the temperature at 1000-1050℃ for 8h. Silicon carbide is obtained.
[0090] Step 4: Compound
[0091] The fluorinated carbon material obtained in step 2 and the silicon carbide obtained in step 3 are ground separately and passed through a 20 μm sieve, mixed, and single-walled carbon nanotubes are added in an amount of 3% of the weight of the prepared porous polypropylene base. The single-walled carbon nanotubes have a diameter of 1 nm to 3 nm, a length of 2 μm to 5 μm, and an aspect ratio of 1000 to 5000. They are fully mixed again to obtain a battery negative electrode material.
[0092] Performance testing:
[0093] The fluorinated silicon carbide composite materials prepared in Examples 1 to 5 and Comparative Example 1 were ground and passed through a 20 μm sieve to obtain 6 types of battery negative electrode materials. The above battery negative electrode materials and the battery negative electrode materials prepared in Comparative Example 2 were used to prepare lithium-ion batteries and perform performance tests, as follows:
[0094] 1. Battery Preparation
[0095] Take 95.0 parts by mass of the negative electrode material of the battery, add 200 parts of an aqueous solution containing 5.0 parts by mass of CMC / SP / PAA (mass ratio 0.5:2.0:2.5) thereto, and mix to form a slurry;
[0096] 2. The slurry is coated on a copper foil with a thickness of 6 μm, dried, and rolled to form an electrode sheet. The thickness of the electrode sheet after pressing is tested and recorded, and recorded as W1.
[0097] 3. Lithium foil was used as the counter electrode to form a soft-pack lithium-ion battery with the copper foil electrode prepared above. The electrolyte used was a solution containing solvents ethylene carbonate (EC) / dimethyl carbonate (DMC) / ethyl methyl carbonate (EMC) (volume ratio of 1:1:1) and 1 mol / L lithium hexafluorophosphate electrolyte. A three-layer microporous diaphragm of polypropylene / polyethylene / polypropylene (PP / PE / PP) was used with a thickness of 20 μm.
[0098] 2. Performance Testing
[0099] 1. The first coulombic efficiency of the lithium-ion battery prepared above was measured at room temperature. The results are shown in Table 1. The current density of charge / discharge was 0.6 mA / cm 2The cut-off charge and discharge voltages are 2.000V and 0.005V.
[0100] 2. Test the capacity retention rate for 100 weeks
[0101] Charge / discharge at a current density of 0.6 mA / cm 2 The cut-off charge and discharge voltage was 2.000 V and 0.005 V, and 100 cycles of charge and discharge were carried out at room temperature. The results were recorded and the capacity retention rate after 100 cycles was calculated. The results are shown in Table 1.
[0102] 3. Expansion rate test:
[0103] After 100 cycles of charge and discharge, the lithium-ion battery was disassembled and the electrode sheet thickness was tested, recorded as W2, and the electrode sheet expansion rate was calculated and recorded in Table 1.
[0104] Electrode sheet expansion rate = (W2-W1) / W1×100%.
[0105] Table 1
[0106] Examples First coulombic efficiency (%) Capacity retention rate after 100 cycles (%) Electrode sheet expansion rate (%) Example 1 91.2 91.64 35.3 Example 2 90.1 85.55 38.7 Example 3 90.5 88.36 34.6 Example 4 90.4 89.10 35.9 Example 5 90.7 88.76 36.8 Comparative Example 1 90.6 78.23 42.5 Comparative Example 2 88.2 75.38 45.3
[0107] From the results in Table 1, we can see that:
[0108] After the batteries were made from the fluorinated silicon carbide composite materials prepared by Examples 1 to 5 of the method of the present invention, the capacity retention rates after 100 cycles were detected to be above 85%, and the electrode sheet expansion rates were below 39%, showing high cycle performance.
[0109] Comparative Example 1 did not use the method of the present invention. The only difference between Comparative Example 1 and Example 1 is that single-walled carbon nanotubes were not added in step 1. The capacity retention rate of the battery produced by the method after 100 cycles dropped to 78.23%, which is much lower than 91.64% of Example 1. The electrode sheet expansion rate was 42.5%, which is much higher than 35.3% of Example 1. It can be seen that the single-walled carbon nanotubes have a supporting and anti-collapse effect on the pore shell of the porous hard carbon, making the restriction of the expansion and contraction deformation of silicon during the cyclic charge and discharge process of the battery more effective, and the cycle performance is improved. In addition, the first coulomb efficiency of Example 1 is also slightly higher than that of Comparative Example 1, indicating that the three-dimensional network structure formed by the single-walled carbon nanotubes also plays a better connecting role in the conduction of current, which is better than the electrical conduction between simple unorganized particles of hard carbon.
[0110] Comparative Example 2 also does not use the method of the present invention. Although the types and amounts of isotactic polypropylene, xylene, butanone, single-walled carbon nanotube slurry, polydimethylsiloxane and perfluoropolyether oil used in Comparative Example 2 and Example 1 are exactly the same, the difference is that the order of addition in each step is different, but the capacity retention rate of the prepared battery after 100 cycles is reduced to 75.38%, which is much lower than 91.64% in Example 1, and the electrode sheet expansion rate is 45.3%, which is much higher than 35.3% in Example 1. It can be seen from the preparation method of the fluorinated silicon carbide composite material in Comparative Example 2 that single-walled carbon nanotube slurry is not added to the porous polypropylene matrix prepared in step 1 of the comparative example, and the single-walled carbon nanotubes of the same mass are compounded in step 4, so the single-walled carbon nanotubes are not fully mixed in the hard carbon to form an effective network skeleton. The fluorinated carbon material prepared in step two is the result of fluorination of the carbon material, but the silicon carbide prepared in step three is not directly fluorinated; the compounding performed in step four is the mixing of the fluorinated carbon material, silicon carbide and single-walled carbon nanotubes. These materials are not organically combined as in the present invention, and therefore no hard carbon conductive shell in the form of pores that limit the expansion of the silicon material, which is interconnected and supported by carbon nanotubes, is formed. Therefore, its deformation limiting effect on the silicon material is not good, and the improvement of the cycle performance is limited.
[0111] It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described above can be combined with each other as long as they do not conflict with each other. In addition, the above are only some embodiments of the present invention, not all embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the scope of protection of the present invention. For example, for the casting method of the casting body in step 2, the method of immersing the porous polymer matrix in the mixed impregnation liquid for natural infiltration can also be used, but it takes a long time to do so. For example, during the infiltration process, when the porous polymer matrix floats in the mixed impregnation liquid, it can be fixed by pressing down with a tool, or the porous polymer matrix can be restricted below the liquid surface by a limiting method.
Claims
1. A method for preparing a fluorinated silicon carbide composite material, characterized in that: The following steps are involved: Step 1, preparing a porous polymer matrix; Add a mixed solution consisting of a polymer, a good solvent and a poor solvent of the polymer in a volume ratio of 10:1 to 5 into a container and stir until a homogeneous solution is formed, add the carbon nanotube slurry and mix evenly; pour into a mold, place in a vacuum oven at 10 to 40°C and stand for 3 to 12 hours, wherein the vacuum degree of the vacuum oven is ≤-90kPa; naturally volatilize the solvent at 20 to 25°C to obtain a porous polymer matrix; wherein the polymer is isotactic polypropylene; Step 2, polydimethylsiloxane and perfluoropolyether oil are mixed evenly at a mass ratio of 10:0.1-0.5 to obtain a mixed impregnation liquid, and then poured into the obtained porous polymer matrix to obtain a casting body; Step 3, the obtained casting body is subjected to the following reactions in sequence to obtain a fluorinated silicon carbide composite material: A. Under vacuum degree ≤ -90kPa, react at 450-600℃ for 6-10h; B. Under inert gas protection, react at 1000-1500℃ for 6-10h.
2. The method for preparing the fluorinated silicon carbide composite material according to claim 1, characterized in that: The good solvent is at least one of xylene, toluene, benzene and decalin; the poor solvent is at least one of butanone, ethanol, methanol, n-butanol and n-propanol.
3. The method for preparing the fluorinated silicon carbide composite material according to claim 2, characterized in that: The mass ratio of the isotactic polypropylene to the carbon nanotubes is 100:1-5.
4. The method for preparing the fluorinated silicon carbide composite material according to claim 1, characterized in that: The perfluoropolyether oil is CF3CF2CF2O(CF(CF3)CF2O)mCF2CF3, and the number average molecular weight is 2000-4500.
5. The method for preparing the fluorinated silicon carbide composite material according to claim 1, characterized in that: The pouring method in step 2 is: A. completely immersing the porous polymer matrix in the mixed impregnation liquid, and then placing it in a vacuum infiltration device; B. Evacuate the mixture, maintain the vacuum degree at -50 to -70 kPa for 30 to 60 seconds, and release the pressure to allow the mixed impregnation liquid to penetrate into the porous polymer matrix; repeat 2 to 3 times.
6. A fluorinated silicon carbide composite material, characterized in that: The porous hard carbon is made by the method of any one of claims 1 to 5, comprising porous hard carbon and fluorinated silicon carbide, wherein the porous hard carbon supports carbon nanotubes, and the pores of the porous hard carbon are filled with the fluorinated silicon carbide.
7. The fluorinated silicon carbide composite material according to claim 6, characterized in that: The carbon nanotubes are single-walled carbon nanotubes.
8. The fluorinated silicon carbide composite material according to claim 7, characterized in that: The single-walled carbon nanotube has a diameter of 1-3 nm, a length of 2-5 μm, and an aspect ratio of 1000-5000.
9. The fluorinated silicon carbide composite material according to claim 6, characterized in that: The porous hard carbon is isotactic polypropylene cracked carbon.
Citation Information
Patent Citations
Surface-modified silicon-carbon composite and preparing method and application thereof
CN109286014A
Preparation method and application of silicon fluoride carbon negative electrode material
CN115799474A
Nano silicon-carbon composite material, preparation method thereof and lithium ion battery negative plate
CN115939342A
Carbon nanotube-containing silicon-carbon composite material as well as preparation method and application thereof
CN116995206A
Silicon carbide negative electrode material and preparation method thereof
CN118782779A